2018
DOI: 10.1002/cbic.201700631
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog Antagonist Pyrimidine–Indole Hybrid Molecule Inhibits Ciliogenesis through Microtubule Destabilisation

Abstract: One of the crucial regulators of embryonic patterning and tissue development is the Hedgehog-glioma (Hh-Gli) signalling pathway; its uncontrolled activation has been implicated in different types of cancer in adult tissues. Primary cilium is one of the important factors required for the activation of Hh signalling, as it brings the critical components together for key protein-protein interactions required for Hh pathway regulation. Most of the synthetic and natural small molecule modulators of the pathway prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
2
7
0
Order By: Relevance
“…Our earlier report [19] suggested that substitution can be incorporated very easily at 1 or 2-position of indole in PIH (P) without changing much in the biological activity. Accordingly, for the synthesis of water soluble derivatives of PIH (P) we then decided to incorporate water soluble moiety in the indole part at this position keeping the hydrazine part of the molecule intact.…”
Section: Chemistrymentioning
confidence: 97%
See 3 more Smart Citations
“…Our earlier report [19] suggested that substitution can be incorporated very easily at 1 or 2-position of indole in PIH (P) without changing much in the biological activity. Accordingly, for the synthesis of water soluble derivatives of PIH (P) we then decided to incorporate water soluble moiety in the indole part at this position keeping the hydrazine part of the molecule intact.…”
Section: Chemistrymentioning
confidence: 97%
“…For the synthesis of N-alkylated indole derivative the reaction was started from 2methylindole-3-carboxaldehyde (3 B). [19] The indole was alkylated with triethylene glycol 2-bromoethyl methyl ether to get N-alkylated indole derivative (4 C). These three indole derivatives were reacted with hydrazine derivative to get the final compounds 6 A, 6 B and 6 C. In accordance with our earlier report, [19] all the compounds were characterized by spectroscopic methods and found to be single-isomers with the appearance of a single set of peaks in 1 HNMR.…”
Section: Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Inspired from the interesting Hh signaling antagonist potency of pyrimidine-indole hybrid (PIH) structure, 54 Khatra et al 55 have designed a small compound library of PIH series 3k (Figure 3B) and identified their distinct modes of action as Hh inhibitors. All the new compounds were screened in Shh-Light 2 cells at 1.0 mM concentration.…”
Section: Recent Advances In Design Of Hh Pathway Inhibitorsmentioning
confidence: 99%